2014
DOI: 10.1016/j.apsusc.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Frictional properties of self-adaptive chromium doped tungsten–sulfur–carbon coatings at nanoscale

Abstract: Transition metal dichalcogenides (TMD) are excellent dry lubricants forming thin (~ 10 nm) tribolayer that simultaneously protects the coating from environmental attack and provides low friction. In this paper, we focus on nanoscale frictional properties of chromium doped tungsten-sulfur-carbon (WSC-Cr) coatings with various Cr content. Friction force microscopy was used to investigate friction force as a function of load. A non-linear contact area dependence on the normal force was observed. The calculated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Indeed, in ultrahigh vacuum the performances of MoS 2 , the most common TMD, are superior to those of graphite [16], which on the contrary performs better in humid environments [17,18]. Furthermore, it was experimentally observed that TMDs can display lower friction coefficients when an external load is applied, at difference to most systems [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in ultrahigh vacuum the performances of MoS 2 , the most common TMD, are superior to those of graphite [16], which on the contrary performs better in humid environments [17,18]. Furthermore, it was experimentally observed that TMDs can display lower friction coefficients when an external load is applied, at difference to most systems [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Zekonyte et al 44,45 on W-S-C and W-S-C-Cr coatings. However, the probe shape can strongly influence the resulting contact properties.…”
Section: Discussionmentioning
confidence: 99%
“…First, we must note that some of the friction measurements with different probes of the same type followed the 2/3 power law (Supporting Information, Figure S4), thus indicating adhesive behavior according to the Hertz-plus offset model, similar to the previously reported results by Zekonyte et al , on W-S-C and W-S-C-Cr coatings. However, the probe shape can strongly influence the resulting contact properties .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 The actual spring constant of the modied tip was calculated by internal built-in thermal noise methods. 34 Normal forces were calibrated by measuring the deection sensitivity (nm V À1 ) from the slope of the linear part of a force-displacement curve obtained on a at silicon surface. The normal force, F N , was set to zero at the point where the cantilever le the surface.…”
Section: Lateral Force Microscopy With Colloidal Probesmentioning
confidence: 99%